Is There a Need to Expand the Refugee Definition? - Cahyana, Intan Nevia; Sabirin, Ahmad (Universitas Muhammadiyah Malang, 2024)
This article examines the urgency of protecting against displacement caused by climate change under international law and questions why Rohingya displacement has not been resolved even though it has been protected by international law, whether the harmonization of human rights approaches, national law, and international law towards refugees and climate refugees. This paper uses a literature review method and a normative legal approach by reviewing national and international human rights law. The findings of this paper suggest that many Rohingya continue to flee to safer countries, often taking enormous risks, including dangerous ocean crossings. The impacts of climate change can be categorized as persecution; the Refugee Convention requires that such persecution be due to race, religion, nationality, political opinion, or membership of a particular social group. Persecution alone is not enough. The difficulty is that the impacts of climate change are largely indiscriminate and not related to specific characteristics such as a person's background or beliefs. The Rohingya people have experienced violence, discrimination, and persecution for decades, and the international community has failed to protect them effectively. The international community has allowed Myanmar to carry out genocide against the Rohingya without taking any action, even though United Nations member states are obliged to protect their population from genocide, war crimes, ethnic cleansing, and crimes against humanity. National, international, and human rights laws play an important role in determining the legal status and rights of refugees in a country. All three must be embedded and integrated, starting from international law and its derivatives to national law, which contains humanitarian rights.